Lived and Learned Experience with Accessible and Inclusive Pedagogy - Brunk, Angie (Association of College & Research Libraries (ACRL), 2023)
I have always walked in two different worlds. Because I am low vision, not blind, I know the joy of seeing and capturing the perfect image in my digital camera’s viewfinder. I know the joy of teaching a dance class. I know what it’s like to be perceived as abled. Because I am low vision, not “normal,” I know the frustration and sometimes humiliation of a teacher caring more about their seating plans or their favorite activity than my ability to participate fully in class. I know the frustration of missing parts of presentations because the presenter did not explain visual content on a slide. I know what it feels like to have an instructor ignore accessibility needs that you have clearly articulated. I know the humiliation of people commenting on the appearance of my eyes. I know what it is to be underestimated or not taken seriously because of preconceived notions about my capabilities.